Vibration of steel framed floors due to running - Ford, Cassandra (Kansas State University, 2016)
Vibration has been a consideration in many types of structures, and as the advancement of technology has allowed steel and concrete sections to become lighter, vibration has become more of a consideration in the design of structures. This report focuses on occupant induced vibration of steel framed floors due to running as the vibration source. The history of vibration analysis and criteria in structures is discussed. However, lack of research and experimentation on running as the source of vibration exists; therefore, the history section focuses on walking as the source of vibration. The current design criteria for vibration of steel framed floors in the United States of America is the American Institute of Steel Construction (AISC) Design Guide 11: Vibrations of Steel Framed Structural Systems Due to Human Activity. This design guide discusses vibration due to walking, running, and rhythmic activities as well as gives design criteria for sensitive occupancies and sensitive equipment. In order to apply the Design Guide 11 analysis procedure for running as the source of vibration, the Kansas State University Chester E. Peters Recreation Complex is used as a case study. The recreation complex includes a 1/5-mile running track that is supported by a composite steel framed floor. Based on the Design Guide 11 criterion, the running track is deemed acceptable. Lastly, this report discusses remedial procedures in the case of annoying floor vibration specific to floors that have running as a source of vibration. In addition, areas of further research are suggested where running is a source of vibration on steel framed floors.
Keywords: Structural floor vibrations; American Institute of Steel Construction Design Guide 11; Running; Indoor running track; Vibration